ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PERMINTAAN AYAM ORGANIK PRODUKSI USAHA DAGANG RAHAYU AK DI KOTA PEKANBARU - Jum'atri Yusri (Universitas Galuh, 2023)
This study aims to analyze the factors that influence consumer demand for organic chicken. This study uses a survey method. The research population is organic chicken consumers UD.Rahayu AK in Pekanbaru City. Research respondents are samples taken by purposive sampling at all outlets selling organic chicken UD. Rahayu AK. Data analysis used multiple linear regression. The results showed that consumers of organic chicken were concentrated at the age of 36-55 years with the average age of consumers being 44 years, the majority were female, the husband and wife's last education level was undergraduate (S1), the husband's occupation was mostly private employees and for wife is a businessman/entrepreneur, has an average household income of Rp 9,057,806/month and has a family of 3-4 people. The factors that are thought to influence the demand for organic chicken in Pekanbaru City are the price of organic chicken, the price of broiler chickens, household income, number of family members, and the length of education of the wife. Together, the effect is statistically significant with an R2 (adj) value of 0.822. Partially, the variables that have a significant effect are household income, number of family members, and wife's length of education with an elasticity coefficient of < 1, which is 0.251; 0.487; 0.424.